Comparative study of Cr3C2-NiCr coatings obtained by HVOF and hard chromium coatings - Guilemany, J. M.; Espallargas, N.; Suegama, P. H.; Benedetti, Assis Vicente [UNESP] (Elsevier B.V., 2006)
In the present work the corrosion resistance of micro-cracked hard chromium and Cr3C2-NiCr (HVOF) coatings applied on a steel substrate have been compared using open-circuit potential (E-OC) measurements, electrochemical impedance spectroscopy (EIS) and polarization curves. The coatings surfaces and cross-section were characterized before and after corrosion tests using optical microscopy (OM) and scanning electron microscopy (SEM). After 18 h of immersion, the open-circuit potential values were around -0.50 and -0.25V/(Ag vertical bar AgCl vertical bar KClsat) for hard chromium and Cr3C2- NiCr, respectively. The surface analysis done after 12 h of immersion showed iron on the hard chromium surface inside/near surface cracks, while iron was not detected on the Cr3C2-NiCr surface even after 18 h. For longer immersion time hard chromium was more degraded than thermal sprayed coating. For hard chromium coating a total resistance values between 50 and 80 k Omega cm(2) were measured and two well-defined time constants were observed, without significant change with the immersion time. For Cr3C2-NiCr coating the total impedance diminished from around 750 to 25 k Omega cm(2) as the immersion time increased from 17 up to 132 h and two overlapped time constants were also observed. Polarization curves recorded after 18 h of immersion showed a lower current and higher corrosion potential for Cr3C2-NiCr coating than other samples studied. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: corrosion resistance; EIS; HVOF; thermal spray; Cr3C2-NiCr; hard chromium